Learning‐Teaching Process Supported by Interactive and Multimedia Resources Development of interactivity, accessibility and usability as elements for increasing the skills of the level of learning and specific skills in secondary school students - POLETTI, Giorgio (Presa Universitară Clujeană, 2020)
Performing a critical and objective analysis of reality is always difficult, but when it comes to the world of children everything is complicated by a kind of nostalgia and impulse to confront what the age represented in our personal experience. It is easy to expire in a moralistic reading of this mounting reality in our society. I also believe that a local reading of the boysʹ world is lacking, because the widespread diffusion of the mass media and the consequent communication society has made this universe uniformly varied and more in need of valorization than of continuous analysis. We are witnessing the multiplication of initiatives that various organizations dedicate to young people, but all too often they satisfy the need of an adult world that needs to feel itself to be a proposer, rather than the actual need to enhance the creative strength of young people.